2009
DOI: 10.1159/000197899
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Prognostic Factor Analysis of 146 Metastatic Neuroendocrine Tumors of the Mid-Gut

Abstract: Background: Gastrointestinal neuroendocrine tumors (NETs) are heterogeneous neoplasms that vary in mortality according to location of primary tumor and stage of disease. Past analyses of survival suggest a trend towards improving longevity among patients with metastatic mid-gut NETs. Methods: We evaluated all cases of metastatic NETs of the mid-gut seen in our institution between 1999 and 2003, measuring survival from time of diagnosis of distant metastatic disease. Median and 5-year survival rates were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 46 publications
7
113
0
4
Order By: Relevance
“…In European and American referral centers, up to 77 and 91 % of patients with PNETs and intestinal NETs [19][20][21][22] present with distant metastases at initial diagnosis, respectively [13]. In the present Japanese study, patients in whom distant metastases were observed at initial diagnosis accounted for 19.9 % of PNETs and 6.0 % of GI-NETs.…”
Section: Discussionmentioning
confidence: 46%
“…In European and American referral centers, up to 77 and 91 % of patients with PNETs and intestinal NETs [19][20][21][22] present with distant metastases at initial diagnosis, respectively [13]. In the present Japanese study, patients in whom distant metastases were observed at initial diagnosis accounted for 19.9 % of PNETs and 6.0 % of GI-NETs.…”
Section: Discussionmentioning
confidence: 46%
“…As a result, it has become increasingly common to identify pancreatic neuroendocrine tumours, with a detection rate exceeding 80% [10]. Finally, although overall survival for patients with pancreatic neuroendocrine tumours is more favourable than for patients with pancreatic adenocarcinomas, the median overall survival in metastatic disease does not exceed 2-5.8 years [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Transduodenal local excision with or without lymph node sampling and pancreaticoduodenectomy are other options for primary treatment of non-metastatic duodenal NETs O2 cm. Nevertheless, the optimal approach remains unclear as the biological behavior of these NETs remains largely unknown (30,31). Although ileum/jejunum NETs often present with metastases at diagnosis, surgical treatment has become increasingly important for their management (32).…”
Section: Management Of Localized Diseasementioning
confidence: 99%